Kualifikasi Pendidikan Perekam Medis dan Informasi Kesehatan di Faskes Tingkat II Masih Belum Memenuhi Standar Profesi: Educational Qualifications for Medical Recorders and Health Information at Level II Health Facilities Still Do Not Meet Professional Standards - Piping Asgiani (Infomasi dan Promosi Kesehatan, 2023)
Introduction: Educational Qualifications of medical recorders are the minimum requirements related to educational background that must be possessed by medical record officers in order to be able to carry out their duties in accordance with their job descriptions in health care facilities. The level of education influences the understanding and ability of officers regarding the security and confidentiality of medical records. Purpose: Know the qualification standards and implementation of job descriptions for medical record officers in hospitals. Method: The type of research used is Qualitative Descriptive research. The research design used is a case study. Determination of research subjects using purposive sampling techniques where the subjects are all medical record officers. The main informants in this study were 4 medical record officers. Results: The number of officers in the medical record section is 35 people. The details per unit are as follows: 8 IT people, 7 RM people and 20 registration officers. Based on educational qualifications, only 4 medical record officers had a D3 Medical Record background, the rest came from SMA, D1 Non RM, D3 Non RM, and S1 Non RM qualifications. The implementation of the job description is in accordance with the organizing guidebook, but there are still several obstacles, namely related to the absence of human resource development, there are double jobs, lack of understanding of confidentiality and delays in returning medical records. Conclusion: There are still educational qualifications that do not have a medical record educational background. There are several obstacles in the implementation of job descriptions, especially for officers who do not have a non-RMIK educational background.